Modification method of yttrium and magnesium ion co-doped lithium vanadium phosphate positive electrode material
Through yttrium magnesium ion co-doping and carbon coating technology, the rate performance and cycling performance of lithium vanadium phosphate materials are improved, the problem of low rate performance of existing materials is solved, and high-performance applications in lithium-ion batteries are realized.
Patent Information
- Application Number
- CN202510003307.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The current lithium vanadium phosphate material has low rate performance, which limits its application in lithium-ion batteries.
By co-doping yttrium ion, carbon coated with yttrium ion doped lithium vanadium phosphate precursor material, and a high-temperature solid-phase sintering method was prepared.
It effectively improves the electronic conductivity, improves the performance and circulation performance of the positive electrode at large magnification, and has a simple process and is suitable for large-scale preparation.
Smart Images

Figure CN119786578A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a modification method of yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material. Background Art
[0002] Lithium-ion batteries have attracted much attention due to their energy density far exceeding that of traditional batteries such as nickel-cadmium batteries. Today, rechargeable lithium-ion batteries are gradually gaining in importance and playing an important role in many fields such as portable electronic devices, grid energy storage and electric vehicles.
[0003] Positive electrode materials are key components of lithium-ion batteries and have a significant impact on battery performance. The development of new positive electrode materials with excellent performance is the direction that people have been working hard on. At present, positive electrode materials mainly include nickel-rich and lithium-rich layered positive electrode materials LiMO2 (M = Ni, Co, Mn, Al, etc.); spinel positive electrode materials LiMn2O4; polyanionic positive electrode materials, such as LiFePO4, etc. Due to their stronger PO bonds and PO4 3D structure, polyanionic positive electrode materials have higher thermal stability than traditional layered transition metal oxides, making them more suitable for use in large lithium-ion batteries.
[0004] Among them, polyanionic lithium iron phosphate materials (LFP) have many advantages such as abundant mineral resources, environmental friendliness, good thermal stability and excellent cycle performance. Therefore, they are suitable for use in new energy vehicles and power grid energy storage. However, their electronic conductivity (~10 -8 S / cm) and ionic conductivity (1.42×10 -15 -2.72×10 -10 S / cm) is low, resulting in low rate performance and specific capacity when charging at high current, which limits the further development of LFP. Compared with LFP, lithium vanadium phosphate material (LVP) has a more open crystal structure, and the lithium ion diffusion rate is higher than LFP. LVP also has excellent electrochemical properties such as higher theoretical specific capacity (133mAh / g (3.0-4.3V); 197mAh / g (3.0-4.8V)), good thermal stability, and higher operating voltage. Because LVP and LFP are both polyanionic compounds with excellent electrochemical properties, improving the performance of lithium vanadium phosphate materials can provide ideas for the modification of lithium iron phosphate, and can even replace lithium iron phosphate materials. Summary of the invention
[0005] The purpose of the present invention is to solve the problem of how to effectively improve the rate performance of lithium vanadium phosphate materials, and to provide a modification method for yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode materials.
[0006] A modification method of a yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material is carried out according to the following steps:
[0007] Step S1: weighing;
[0008] According to the molar ratio of lithium, vanadium, phosphorus, yttrium, magnesium and carbon being 3.15:(1.8-1.96):3:(0.02-0.1):(0.02-0.1):3.5, lithium source, vanadium source, phosphorus source, yttrium source, magnesium source and carbon source are weighed respectively;
[0009] Step S2: preparing a carbon-coated yttrium magnesium ion-doped lithium vanadium phosphate precursor material;
[0010] The lithium source, vanadium source, phosphorus source, yttrium source, magnesium source and carbon source weighed in step S1 are added to the ethanol solution, and stirred to obtain a mixture; the mixture is placed in a ball mill, and fully ball-milled to obtain a slurry; the slurry is dried and ground to obtain a carbon-coated yttrium magnesium ion-doped lithium vanadium phosphate precursor material;
[0011] Step S3:
[0012] The carbon-coated yttrium-magnesium ion-doped lithium vanadium phosphate precursor material obtained in step S2 is placed in a tube furnace and subjected to gradient high-temperature calcination in an inert gas atmosphere. After the calcination, it is naturally cooled to room temperature, and finally ground and sieved to obtain a yttrium-magnesium ion-co-doped lithium vanadium phosphate positive electrode material with a chemical formula of Li 3.15 V 1.8~1.96 Y 0.02~0.1 Mg 0.02~0.1 (PO4)3 / C.
[0013] Beneficial effects of the present invention:
[0014] (1) The present invention provides a method for modifying lithium vanadium phosphate positive electrode materials, wherein the lithium vanadium phosphate positive electrode materials are co-doped with metal elements yttrium and magnesium. The doping of metal elements yttrium and magnesium effectively improves the electronic conductivity, realizes rapid electronic conduction between particles, is beneficial to the ion / electron exchange of active substances, greatly improves the performance of the positive electrode at high rates, and has cycle performance. The preparation is simple, easy to control, and has a short synthesis cycle, and has good application prospects.
[0015] (2) The present invention utilizes a high-temperature solid-phase sintering method to directly synthesize yttrium and magnesium co-doped modified LVP positive electrode materials, which has the advantages of being simple and efficient, and provides a possible industrialization route; the lithium vanadium phosphate compound prepared by the present invention exhibits good cycle stability and rate performance as a positive electrode material in lithium-ion batteries; the equipment and process flow of the present invention are simple, the product consistency is high, and it is suitable for large-scale mass preparation of positive electrode material powders.
[0016] (3) This invention uses LVP material as the research material, aiming to improve the rate performance of lithium-ion batteries. By optimizing the synthesis process and performing ion doping, regulating the crystal morphology, and revealing the influence of material structure on rate performance, the research results will provide help for the preparation of high-rate batteries.
[0017] (4) The method of the present invention uses ethanol as a ball milling dispersant, which shortens the time required for the drying process, reduces the temperature required for drying, and better controls the drying process.
[0018] The invention can obtain a modification method of yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The XRD pattern of the yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material prepared in Example 1 is shown;
[0020] Figure 2 A scanning electron microscope image showing the yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material prepared in Example 1;
[0021] Figure 3 A scanning electron microscope image showing the lithium vanadium phosphate positive electrode material not doped with yttrium and magnesium in Comparative Example 1;
[0022] Figure 4 The initial charge and discharge curve of the yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material prepared in Example 1 under 1C condition;
[0023] Figure 5 A graph showing the rate performance of the yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material prepared in Example 1;
[0024] Figure 6 A graph showing the 1C constant current cycling performance of the yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material prepared in Example 1;
[0025] Figure 7 The AC impedance spectrum of the yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material prepared in Example 1 is shown;
[0026] Figure 8 The cyclic voltammetry curve of the yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material prepared in Example 1 is shown. DETAILED DESCRIPTION
[0027] Specific implementation method 1: In this implementation method, a modification method of a yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material is carried out according to the following steps:
[0028] Step S1: weighing;
[0029] According to the molar ratio of lithium, vanadium, phosphorus, yttrium, magnesium and carbon being 3.15:(1.8-1.96):3:(0.02-0.1):(0.02-0.1):3.5, lithium source, vanadium source, phosphorus source, yttrium source, magnesium source and carbon source are weighed respectively;
[0030] Step S2: preparing a carbon-coated yttrium magnesium ion-doped lithium vanadium phosphate precursor material;
[0031] The lithium source, vanadium source, phosphorus source, yttrium source, magnesium source and carbon source weighed in step S1 are added to the ethanol solution, and stirred to obtain a mixture; the mixture is placed in a ball mill, and fully ball-milled to obtain a slurry; the slurry is dried and ground to obtain a carbon-coated yttrium magnesium ion-doped lithium vanadium phosphate precursor material;
[0032] Step S3:
[0033] The carbon-coated yttrium-magnesium ion-doped lithium vanadium phosphate precursor material obtained in step S2 is placed in a tube furnace and subjected to gradient high-temperature calcination in an inert gas atmosphere. After the calcination, it is naturally cooled to room temperature, and finally ground and sieved to obtain a yttrium-magnesium ion-co-doped lithium vanadium phosphate positive electrode material with a chemical formula of Li 3.15 V 1.8~1.96 Y 0.02~0.1 Mg 0.02~0.1 (PO4)3 / C.
[0034] Specific embodiment 2: The difference between this embodiment and specific embodiment 1 is that the ratio of the total mass of the lithium source, vanadium source, phosphorus source, yttrium source, magnesium source and carbon source described in step S2 to the volume of the ethanol solution is 1g: (30-60)mL.
[0035] The other steps are the same as those in the first specific implementation.
[0036] Specific embodiment three: The difference between this embodiment and specific embodiment one or two is that: the lithium source is lithium hydroxide monohydrate, lithium dihydrogen phosphate or lithium carbonate; the vanadium source is vanadium pentoxide; the phosphorus source is lithium dihydrogen phosphate or ammonium dihydrogen phosphate; the yttrium source is yttrium oxide; the magnesium source is magnesium oxide; and the carbon source is sucrose or glucose.
[0037] The other steps are the same as those in the first or second embodiment.
[0038] Specific implementation method 4: The difference between this implementation method and specific implementation methods 1 to 3 is that the stirring in step S2 adopts electromagnetic stirring, and the stirring time is 0.5 to 2 hours.
[0039] The other steps are the same as those in Specific Embodiments 1 to 3.
[0040] Specific embodiment five: The difference between this embodiment and specific embodiments one to four is that: the temperature condition during ball milling in step S2 is 20-25°C, the ball milling speed is 400-600r / min, and the ball milling time is 6-10h; the ball mill uses steel balls, agate balls or zirconia balls, and the mass ratio of balls to solid materials is (15-25):1.
[0041] The other steps are the same as those in Specific Embodiments 1 to 4.
[0042] Specific embodiment 6: The difference between this embodiment and specific embodiments 1 to 5 is that in step S2, the slurry is placed in a blast drying oven and dried at 80 to 120°C for 1 to 3 hours.
[0043] The other steps are the same as those in Specific Embodiments 1 to 5.
[0044] Specific embodiment 7: The difference between this embodiment and specific embodiments 1 to 6 is that the grinding in step S2 is performed in an agate mortar for 20 to 30 minutes.
[0045] The other steps are the same as those in Specific Embodiments 1 to 6.
[0046] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the inert gas described in step S3 is argon gas.
[0047] The other steps are the same as those in Specific Embodiments 1 to 7.
[0048] Specific embodiment nine: The difference between this embodiment and specific embodiments one to eight is that the gradient high-temperature calcination in step S3 is carried out according to the following steps: first, the temperature is increased to 300-400°C at a heating rate of 4-8°C / min, and kept at 300-400°C for 4-10h; after the insulation is completed, the temperature is increased to 750-850°C at a heating rate of 4-8°C / min, and the temperature is continued to be kept at 750-850°C for 6-10h.
[0049] The other steps are the same as those in Specific Embodiments 1 to 8.
[0050] Specific embodiment 10: The difference between this embodiment and specific embodiments 1 to 9 is that after cooling to room temperature in step S3, grinding is performed for 20 to 30 minutes and then passed through a 400-mesh sieve.
[0051] The other steps are the same as those in Specific Embodiments 1 to 9.
[0052] The following examples are used to verify the beneficial effects of the present invention:
[0053] Example 1: A method for modifying a positive electrode material co-doped with yttrium and magnesium ions and lithium vanadium phosphate, comprising the following steps:
[0054] Step S1: weighing;
[0055] According to the molar ratio of lithium, vanadium, phosphorus, yttrium, magnesium and carbon being 3.15:1.88:3:0.06:0.06:3.5, lithium carbonate, vanadium pentoxide, diammonium phosphate, yttrium oxide, magnesium oxide and glucose were weighed respectively;
[0056] Step S2: preparing a carbon-coated yttrium magnesium ion-doped lithium vanadium phosphate precursor material;
[0057] The lithium carbonate, vanadium pentoxide, ammonium dihydrogen phosphate, yttrium oxide, magnesium oxide and glucose weighed in step S1 are added to 43 mL of ethanol solution, and electromagnetically stirred for 0.5 h to obtain a mixture; the mixture is placed in a ball mill, and the ball milling time is 8 h at a temperature of 25° C. and a speed of 500 r / min to obtain a slurry, and the ball milling uses zirconium oxide balls, and the mass ratio of the balls to the solid material is 20:1; the slurry is placed in a blast drying oven, dried at 80° C. for 2 h, and then ground in an agate mortar for 20 min to obtain a carbon-coated yttrium magnesium ion-doped lithium vanadium phosphate (LVYMP / C) precursor material in the form of a green powder;
[0058] Step S3:
[0059] The carbon-coated yttrium-magnesium-ion-doped lithium vanadium phosphate precursor material obtained in step S2 is placed in a tube furnace, and is first heated to 400°C at a heating rate of 5°C / min under an argon atmosphere, and is kept at 400°C for 4 hours; after the insulation is completed, it is heated to 800°C at a heating rate of 5°C / min, and is kept at 800°C for 8 hours; after the calcination is completed, it is naturally cooled to room temperature, and finally ground for 30 minutes, and then passed through a 400-mesh sieve to obtain a yttrium-magnesium-ion-co-doped lithium vanadium phosphate positive electrode material with a chemical formula of Li 3.15 V 1.88 Y 0.06 Mg 0.06 (PO4)3 / C.
[0060] Comparative Example 1:
[0061] The preparation method provided in Example 1 is used, except that no metal compounds of yttrium and magnesium are added to the raw materials, and finally a general formula of Li 3.15 V2(PO4)3 / C is a positive electrode material for lithium-ion batteries.
[0062] The materials obtained in Example 1 and Comparative Example 1 were respectively used as positive electrode materials for lithium-ion batteries, mixed with a conductive agent (acetylene black) and a binder (PVDF) in a volume ratio of 8:1:1 to obtain a slurry, and then coated on a metal aluminum current collector to obtain a positive electrode, and polyolefin was used as a separator, metal lithium was used as a counter electrode, 1 mol / L LiPF6 was used as an electrolyte as a solute, ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 were used as solvents, and 5% fluoroethylene carbonate (FEC) was used as an additive. The lithium-ion battery was assembled in a glove box filled with argon.
[0063] The assembled lithium-ion battery was left to stand for 12 hours and then subjected to constant current charge and discharge tests. The charge and discharge voltage window was 3 to 4.2 V. The specific capacity, rate performance, and long cycle performance of the positive electrode of the lithium-ion battery were measured at room temperature.
[0064] The LVYMP / C material obtained in Example 1 was structurally characterized. Figure 1 The XRD pattern of the yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material prepared in Example 1 is shown; Figure 1 As shown, all diffraction peak positions of LVYMP / C material are consistent with those of standard card LVP JCPDS#:80-1515, belonging to the monoclinic phase structure of pnma space group and no impurity peaks are detected, indicating that the introduction of yttrium and magnesium ions does not affect the crystal structure of the material.
[0065] Figure 2 The scanning electron microscope image of the yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material prepared in Example 1 is shown. Figure 3 The scanning electron microscope image of the lithium vanadium phosphate positive electrode material not doped with yttrium and magnesium in Comparative Example 1 is shown; Figure 2-3 As shown, there is no obvious difference in the microscopic morphology between the undoped lithium vanadium phosphate material and the lithium vanadium phosphate material co-doped with yttrium and magnesium ions. This shows that the doping modification of yttrium and magnesium ions has no obvious effect on the microscopic morphology of the lithium vanadium phosphate material, and the material still maintains its original morphology.
[0066] Figure 4 The initial charge and discharge curve of the yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material prepared in Example 1 under 1C conditions; Figure 4 As shown in the figure, the initial discharge capacity of the lithium-ion battery made of LVYMP / C material at a current density of 1C is increased from 99.9mAh / g to 105.6mAh / g. This is because the replacement of vanadium by yttrium and magnesium ions will lead to the appearance of electron holes in the crystal structure, thereby establishing a p-type conductive mechanism in the structure, improving the electronic conductivity of the material, and thus improving the discharge capacity of the material; at the same time, the doping of magnesium ions will reduce the unit cell volume of lithium vanadium phosphate, which is beneficial to alleviate the unit cell volume shrinkage caused by the escape of lithium ions and improve the structural stability of the material.
[0067] Figure 5 The figure shows the rate performance of the yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material prepared in Example 1; Figure 5 As shown in the figure, the lithium-ion battery made of LVYMP / C material has improved conductivity of the material due to the doping of yttrium and magnesium ions, and thus exhibits good rate performance. After cycling from 0.1C to 10C and then back to 0.1C, the discharge specific capacity can still be restored to the initial level, proving that the material has good reversibility.
[0068] Figure 6 1C constant current cycling performance diagram of the yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material prepared in Example 1; Figure 6 As shown in the figure, the lithium-ion battery made of LVYMP / C material has good cycle stability due to the reduction of the unit cell volume and the improvement of the material stability. The initial discharge specific capacity is 105.6 mAh / g at a current density of 1C, and the capacity is 103.9 mAh / g after 400 cycles, with a capacity retention rate of up to 98.4%.
[0069] Figure 7 The AC impedance spectrum of the yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material prepared in Example 1 is shown; Figure 7 As shown, the lithium-ion battery made of LVYMP / C material has lower impedance and better diffusion rate.
[0070] Figure 8 The cyclic voltammetry curve of the yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material prepared in Example 1 is shown; from the cyclic voltammetry curve of the lithium ion battery made of LVYMP / C material in the figure, it can be seen that the lithium ion battery made of LVYMP / C material has good cycle reversibility.
Claims
1. A method for modifying a positive electrode material co-doped with yttrium and magnesium ions and containing lithium vanadium phosphate, characterized in that The modification method is carried out according to the following steps: Step S1: weighing; According to the molar ratio of lithium, vanadium, phosphorus, yttrium, magnesium and carbon being 3.15:(1.8-1.96):3:(0.02-0.1):(0.02-0.1):3.5, lithium source, vanadium source, phosphorus source, yttrium source, magnesium source and carbon source are weighed respectively; Step S2: preparing a carbon-coated yttrium magnesium ion-doped lithium vanadium phosphate precursor material; The lithium source, vanadium source, phosphorus source, yttrium source, magnesium source and carbon source weighed in step S1 are added to the ethanol solution, and stirred to obtain a mixture; the mixture is placed in a ball mill, and fully ball-milled to obtain a slurry; the slurry is dried and ground to obtain a carbon-coated yttrium magnesium ion-doped lithium vanadium phosphate precursor material; Step S3: The carbon-coated yttrium-magnesium ion-doped lithium vanadium phosphate precursor material obtained in step S2 is placed in a tube furnace and subjected to gradient high-temperature calcination in an inert gas atmosphere. After the calcination, it is naturally cooled to room temperature, and finally ground and sieved to obtain a yttrium-magnesium ion-co-doped lithium vanadium phosphate positive electrode material with a chemical formula of Li 3.15 V 1.8~1.96 Y 0.02~0.1 Mg 0.02~0.1 (PO4)3 / C.
2. The method for modifying a yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material according to claim 1, characterized in that The ratio of the total mass of the lithium source, vanadium source, phosphorus source, yttrium source, magnesium source and carbon source described in step S2 to the volume of the ethanol solution is 1 g: (30-60) mL.
3. The method for modifying a yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material according to claim 1 or 2, characterized in that The lithium source is lithium hydroxide monohydrate, lithium dihydrogen phosphate or lithium carbonate; the vanadium source is vanadium pentoxide; the phosphorus source is lithium dihydrogen phosphate or ammonium dihydrogen phosphate; the yttrium source is yttrium oxide; the magnesium source is magnesium oxide; and the carbon source is sucrose or glucose.
4. The method for modifying a yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material according to claim 1, characterized in that In step S2, electromagnetic stirring is used for stirring, and the stirring time is 0.5 to 2 hours.
5. The method for modifying a yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material according to claim 1, characterized in that The temperature condition during ball milling in step S2 is 20-25° C., the ball milling speed is 400-600 r / min, and the ball milling time is 6-10 h; the ball mill uses steel balls, agate balls or zirconia balls, and the mass ratio of balls to solid materials is (15-25):
1.
6. The method for modifying a yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material according to claim 1, characterized in that In step S2, the slurry is dried in a forced air drying oven at 80 to 120° C. for 1 to 3 hours.
7. The method for modifying a yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material according to claim 1, characterized in that The grinding in step S2 is performed in an agate mortar for 20 to 30 minutes.
8. The method for modifying a yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material according to claim 1, characterized in that The inert gas described in step S3 is argon.
9. The method for modifying a yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material according to claim 1, characterized in that In step S3, the gradient high-temperature calcination is carried out according to the following steps: first, the temperature is increased to 300-400°C at a heating rate of 4-8°C / min, and the temperature is kept at 300-400°C for 4-10 hours; after the insulation is completed, the temperature is increased to 750-850°C at a heating rate of 4-8°C / min, and the temperature is continued to be kept at 750-850°C for 6-10 hours.
10. The method for modifying a yttrium-magnesium ion co-doped lithium vanadium phosphate positive electrode material according to claim 1, characterized in that After cooling to room temperature in step S3, the mixture is ground for 20 to 30 minutes and then passed through a 400-mesh sieve.
Citation Information
Patent Citations
Preparation method of positive material of lithium-ion battery for portable game machine
CN103199260A
Method for preparing magnesium-doped lithium vanadium phosphate cathode material
CN104319374A
Preparation method of lithium ion battery positive electrode material Li3V2(PO4)3
CN104466176A
Ternary blended positive electrode material, preparation method therefor and battery
WO2023174435A1